2020
DOI: 10.2459/jcm.0000000000001043
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate dose of nonvitamin-K antagonist oral anticoagulants: prevalence and impact on clinical outcome in patients with nonvalvular atrial fibrillation

Abstract: Background Limited real-world data are available regarding the outcome of patients treated with inappropriate dose of nonvitamin-K antagonist oral anticoagulants (NOACs). Objective To assess the prevalence and factors associated with inappropriate dose prescription of NOACs and to evaluate adverse events that come from this inappropriate prescription. Methods Single-center multidisciplinary registry includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Inappropriate dosing of NOACs has been associated with increased thromboembolism and mortality in AF patients [21] , [22] , [23] (Godino2020, Camm2020, Steinberg2018). In accordance with these publications, we found that the rate of undertreatment with NOACs was higher in the deceased.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate dosing of NOACs has been associated with increased thromboembolism and mortality in AF patients [21] , [22] , [23] (Godino2020, Camm2020, Steinberg2018). In accordance with these publications, we found that the rate of undertreatment with NOACs was higher in the deceased.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate dosing is not uncommon with NOACs. Use of off-label dosing regimen may be influenced by various factors including clinician perception of higher bleeding risk and lack of familiarity with dosing guidelines [19,20]. More commonly, inappropriate low dosing has been reported in studies exploring daily practice of NOACs [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the other DOACs, in which dose adjustment was performed in the phase III clinical trials, in RE-LY, patients were randomized to receive either dabigatran 150 mg or 110 mg, but no dose adjustment was required [8,[46][47][48]. A great concern with DOACs is the prescription of inappropriate doses that could translate into more events [49]. However, our study showed that in clinical practice, both doses of dabigatran seem effective and safe.…”
Section: Discussionmentioning
confidence: 99%